2016
DOI: 10.1027/2151-2604/a000255
|View full text |Cite
|
Sign up to set email alerts
|

How Effective are Behavior Change Interventions Based on the Theory of Planned Behavior?

Abstract: Abstract. The theory of planned behavior (TPB) is a prominent framework for predicting and explaining behavior in a variety of domains. The theory is also increasingly being used as a framework for conducting behavior change interventions. In this meta-analysis, we identified 82 papers reporting results of 123 interventions in a variety of disciplines. Our analysis confirmed the effectiveness of TPB-based interventions, with a mean effect size of .50 for changes in behavior and effect sizes ranging from .14 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
272
3
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 426 publications
(341 citation statements)
references
References 112 publications
(77 reference statements)
12
272
3
20
Order By: Relevance
“…As mentioned above, previous smoking interventions claiming to be based on the TPB usually lack evidence to support this assertion (Hardeman et al, 2002;Sutton, 2015). TPB-based interventions have successfully changed a number of health behaviours (Steinmetz et al, 2016) but, as the findings of Study 2 showed, adolescent smoking is a behaviour involving various contextual factors. Therefore, although the TPB provides a framework to understand adolescent smoking in China, to achieve the successful changes in attitude, subjective norm, and perceived behavioural control might need considerations of other layers rather than only focusing on the constructs (Ingham, 1993;Mielewczyk & Willig, 2007).…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned above, previous smoking interventions claiming to be based on the TPB usually lack evidence to support this assertion (Hardeman et al, 2002;Sutton, 2015). TPB-based interventions have successfully changed a number of health behaviours (Steinmetz et al, 2016) but, as the findings of Study 2 showed, adolescent smoking is a behaviour involving various contextual factors. Therefore, although the TPB provides a framework to understand adolescent smoking in China, to achieve the successful changes in attitude, subjective norm, and perceived behavioural control might need considerations of other layers rather than only focusing on the constructs (Ingham, 1993;Mielewczyk & Willig, 2007).…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 99%
“…Looking at the development of the TPB itself, of note is that Ajzen (1991) has realised this importance of context as he has incorporated PBC into a former theory and emphasised specific context, Health conception National contexts, history, tobacco price Social meanings, media Psychological theories time, and participants. Although the TPB is often categorised as a social cognition theory operating at an individual level, a review of TPB-based interventions found that programmes have better outcomes when they are conducted in groups rather than individuals (Steinmetz et al, 2016). However, how to specifically manage the contextual factors and group dynamics is definitely beyond the TPB.…”
Section: Figure 9 From Psychological Theories To Wider Social Factorsmentioning
confidence: 99%
See 3 more Smart Citations